2021
DOI: 10.1186/s12905-021-01212-9
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of sexual life among breast cancer survivors at reproductive age

Abstract: Background Our understanding of the experiences of women at reproductive age regarding sexual life and issues they may face after starting the treatment of breast cancer is limited. Therefore, this qualitative study aimed to explore sexual life and its related issues among breast cancer survivors at reproductive age in Iran. Methods A qualitative research was conducted. Participants were 21 breast cancer survivors who were under 51 years of age tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 44 publications
4
35
1
1
Order By: Relevance
“…Age at breast cancer diagnosis is also significantly lower compared to the rest of the world, and many Iranian patients are still in their reproductive years [ 3 ]. In addition, studies have shown that Iranian breast cancer survivors do not receive sufficient information regarding reproductive health [ 32 ] and almost no information regarding sexual health [ 33 ]. Therefore, the development of this guideline will be extremely beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Age at breast cancer diagnosis is also significantly lower compared to the rest of the world, and many Iranian patients are still in their reproductive years [ 3 ]. In addition, studies have shown that Iranian breast cancer survivors do not receive sufficient information regarding reproductive health [ 32 ] and almost no information regarding sexual health [ 33 ]. Therefore, the development of this guideline will be extremely beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Karin et al suggested that treatment-induced symptoms, depression, and age were predictors of sexual problems [26]. Through a qualitative study, Maryam et al indicated that adverse sexual function (vaginal dryness or pain, changes in sexual desire, and decreased sexual arousal) leads to decreased sexual satisfaction among survivors [27]. Jennifer et al concluded that a quarter of couples are not having sex because they are uninterested in it (78%) and too tired (44%) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual function is a fundamental aspect of patients’ well-being. 57 BC treatment modalities can lead to various sexual changes among BC survivors. 58–60 Locoregional treatments, including surgery and radiotherapy, can produce intense emotional distress, cause a detrimental change in body image, and reduce sensitivity in the breasts.…”
Section: Body Image and Sexual Function/satisfactionmentioning
confidence: 99%
“…Four main barriers leading to an unfulfilled sexual experience were identified: a) undesirable sexual function, characterized by decreased sexual desire, arousal and satisfaction, less frequent sexual relationships, and perception of diminished sexual attractiveness; b) context-based beliefs, including religious, cultural and family beliefs; c) unmet information and support needs by health care providers; and d) emotional crisis, with feelings of loss of femininity and guilt. 57 …”
Section: Body Image and Sexual Function/satisfactionmentioning
confidence: 99%